“An illness of isolation, a disease of disconnection”: Depression and the erosion of we-experiences - Osler, Lucy (Frontiers in Psychology, 2022)
Depression is an affective disorder involving a significant change in an individual’s emotional and affective experiences. While the DSM mentions that social impairment may occur in depression, first-person reports of depression consistently name isolation from others as a key feature of depression. I present a phenomenological analysis of how certain interpersonal relations are experienced in depression. In particular, I consider whether depressed individuals are able to enter into ‘we-experiences’ with other people. We-experiences are experiences had with two or more people as a we (rather than having an experience as an I), experiences that allow one to enter into robustly shared experiences with others. I claim that the ability to enter into we-experiences (both actual and habitual) is eroded in depression due to an overwhelming feeling of being different to and misunderstood by others. As such, I suggest that depression should be conceived of as fixing an individual in their first-person singular perspective, thus inhibiting their ability to experience in the first-person plural and to feel a sense of connectedness or togetherness with others as part of a we. By attending to on-going impacts of a diminished ability to enter into we-experiences, we can provide a situated and more nuanced account of the changes of interpersonal relations in depression that captures the progressive (rather than static) nature of the disorder. In turn, this analysis furthers our understanding of the emergence, frustration, and erosion of actual and habitual we-experiences.